Effect of Guided Inquiry and Explicit-Instructional Strategies on Lower Basic Students’ Academic Performance in Mathematics - Ogunjimi, Mayowa Olurotimi; Gbadeyanka, Taofeek Akolade (Universitas Pendidikan Indonesia (UPI), 2023)
This study investigated the effect of guided inquiry and explicit-instructional strategies on lower basic students’ academic performance in mathematics. We employed a non-randomized pretest-posttest control group quasi-experimental design. The population comprised all primary school students in Oyo East Local Government Area, Nigeria while 132 students all in lower basic schools were sampled from six intact classes. The mathematics Performance Test (MPT) was used as a research instrument. The content validity was established with the use of experts’ judgment from two experts in mathematics education while the test-retest reliability estimates of the instrument yielded 0.78. Four research hypotheses were tested. The findings of the study revealed that there is a significant main effect in using a guided-inquiry instructional strategy on mathematics. There is the significant main effect of explicit instructional strategy on students’ mathematics academic performance. There is a significant interaction effect of guided inquiry and explicit instructional strategies, gender, and school type on lower basic students’ academic performance. Guided inquiry and explicit instructional strategies are good teaching strategies to reduce mathophobia among primary school students in mathematics.